A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.